OCT ANGIOGRAPHY AND ITS ROLE IN THE STUDY OF RETINAL MICROCIRCULATION IN GLAUCOMA (PART TWO) - N. I. Kurysheva (Российский офтальмологический журнал)
A new diagnostic method of ocular microcirculatory bloodstream - optical coherence tomography angiography (OCTA) has helped obtain new information on the anatomy and physiology of microcirculatory bloodstream of the retina and the optic disc. The review provides literary data on the reduction in peripapillary and macular blood flow in various glaucoma stages. These changes are shown to correlate with structural and functional disorders. It is emphasized that OCTA is a prospective method for early detection of glaucoma and for glaucoma monitoring. For citation: Kurysheva N.I. OCT angiography and its role in the study of retinal microcirculation in glaucoma (part two). Russian ophthalmological journal. 2018; 11 (3): 95-100 (In Russian). doi: 10.21516/2072-0076-2018-11-3-95-100